2011
DOI: 10.1002/sia.3734
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of 5,10,15,20‐tetraphenylporphyrin Langmuir films for gas chemsensor applications

Abstract: In this work is reported the preparation and characterization of 5,10,15,20-tetraphenylporphyrin (H 2 TPP) films at the water-air interfaces. The surface pressure-area isotherms (π -A) and UV-Vis spectroscopy were used to investigate the effect of the spreading methods and parameters on the porphyrin monolayer formation. Also, Langmuir-Blodgett (LB) and LangmuirSchaefer (LS) films were deposited onto glass substrates in order to study the conformation changes in porphyrin molecular packing. Quartz crystal micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
(59 reference statements)
0
5
0
Order By: Relevance
“…Mansur et al prepared a Langmuir film of 5,10,15,20tetraphenylporphyrin and transferred it to a QCM sensor for detection of NO 2 gas. 156 Capan et al reported gas sensing properties of LB films of metal free 2,3,7,8,12,13,17,18octaethyl-21H,23H-porphine and its derivatives containing iron chloride, cobalt and magnesium. 157 Sensing capabilities of these thin films for volatile organic compounds such as chloroform, benzene, toluene and ethyl alcohol were investigated using the QCM technique.…”
Section: Othersmentioning
confidence: 99%
“…Mansur et al prepared a Langmuir film of 5,10,15,20tetraphenylporphyrin and transferred it to a QCM sensor for detection of NO 2 gas. 156 Capan et al reported gas sensing properties of LB films of metal free 2,3,7,8,12,13,17,18octaethyl-21H,23H-porphine and its derivatives containing iron chloride, cobalt and magnesium. 157 Sensing capabilities of these thin films for volatile organic compounds such as chloroform, benzene, toluene and ethyl alcohol were investigated using the QCM technique.…”
Section: Othersmentioning
confidence: 99%
“…It is worth noting that, in any case, MPor, as a typical organic semiconductor, is more sensitive to NO 2 than the Zr 6 cluster. As a matter of fact, the sensing performance of PCN-222-Cu is significantly improved compared to those of metalloporphyrin-based molecular semiconductors. This is not only attributed to the unique one-dimensional mass transfer channel offered by PCN-222-M that can promote continuity of the conductive pathway of the sensing system, but more importantly the formation of MPor/Zr 6 cluster hybrid materials that provide a free hole reservoir (buffer effect) at the MPor/Zr 6 interface to boost the sensing performance …”
Section: Resultsmentioning
confidence: 99%
“…The method of film deposition is chosen depending on the properties of the compounds. Films of porphyrins and phthalocyanines soluble in organic solvents are deposited by spin coating [1], Langmuir-Blodgett (LB), and Langmuir-Schaefer (LS) [32][33][34] methods, while compounds that are volatile in a vacuum are deposited by vacuum deposition methods, namely physical vapor deposition (PVD) or organic molecular beam deposition (OMBD) [35,36]. To prepare active layers for SPR sensors, thin films of porphyrins and phthalocyanines of various metals are deposited on a substrate covered with gold or silver.…”
Section: Spr Sensorsmentioning
confidence: 99%